2007
DOI: 10.1590/s0101-31222007000100022
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes de Senna siamea (Lam.) H.S. Irwin E Barneby: Caesalpinoideae

Abstract: ALEK SANDRO DUTRA 2 , SEBASTIÃO MEDEIROS FILHO 3 , ELIZITA MARIA TEÓFILO 4 , FÁBIO OLIVEIRA DINIZ 5 RESUMO -Senna siamea é uma espécie arbórea originária da Tailândia, que se adaptou às condições do nordeste brasileiro, que vem sendo utilizada na arborização, cerca viva e produção de madeira. A pesquisa foi conduzida em dois experimentos com o objetivo de identificar métodos para superação da dormência e verificar os efeitos da temperatura e luz na germinação de suas sementes. No primeiro, as sementes foram su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
4
0
5
Order By: Relevance
“…speciosa Schrad., C. spectabilis DC., C. splendida Vogel, C. tora L., now are included in Senna or Chamaecrista (see Fig. 1) and exclusively produce seeds with PY (see Faruqi et al 29 , Martin et al 30 , Rizzini 31 , Bhatia et al 32 , Zegers and Lechuga 33 , Daiya et al 34 , Teem et al 35 , Gill et al 16 , Felippe and Polo 36 , Kay et al 37 , Khan et al 38 , Cissé 39 ; Al-Helal et al 40 , Elberse and Breman 41 , Bhattacharya and Saha 42 , Rodrigues et al 43 , Capelanes 44 , Todaria and Negi 19 , Francis and Rodriguez 45 , Lezama et al 46 , Agboola 47 , Baskin et al 48 , Jeller and Perez 49 , Fowler and Bianchetti 50 , Bargali and Singh 51 , Dutra et al 52 , Ellis et al 53 , Baskin and Baskin 9 , Mishra and Bohra 54 , Rodrigues-Junior et al 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…speciosa Schrad., C. spectabilis DC., C. splendida Vogel, C. tora L., now are included in Senna or Chamaecrista (see Fig. 1) and exclusively produce seeds with PY (see Faruqi et al 29 , Martin et al 30 , Rizzini 31 , Bhatia et al 32 , Zegers and Lechuga 33 , Daiya et al 34 , Teem et al 35 , Gill et al 16 , Felippe and Polo 36 , Kay et al 37 , Khan et al 38 , Cissé 39 ; Al-Helal et al 40 , Elberse and Breman 41 , Bhattacharya and Saha 42 , Rodrigues et al 43 , Capelanes 44 , Todaria and Negi 19 , Francis and Rodriguez 45 , Lezama et al 46 , Agboola 47 , Baskin et al 48 , Jeller and Perez 49 , Fowler and Bianchetti 50 , Bargali and Singh 51 , Dutra et al 52 , Ellis et al 53 , Baskin and Baskin 9 , Mishra and Bohra 54 , Rodrigues-Junior et al 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…[11] studied treatments to overcome dormancy of Sterculia striata concluded that scarification with sandpaper number 80 on the opposite side of micropylar favors the percentage of seedlings in the first count, and recommended rapid and uniform emergence of seeds of Sterculia striata, but the mechanical scarification no increases germination of the studied species, however, in other species the scarification with sandpaper favors the germination of seeds that have water-impermeable seed coat, as well as seeds of Senna macranthera [12], Ocotea corymbosa [13], Leucaena diversifolia [14], Operculina macrocarpa [15], Acacia mearnsii [16], Ormosia arborea [17], Schizolobium amazonicum [18], Leucaena leucocephala [7] and Senna siamea [19].…”
Section: Resultsmentioning
confidence: 99%
“…El elevado porcentaje de semillas duras al finalizar el ensayo indica que este método es insuficiente para superar la barrera física de la cubierta seminal, ya que las semillas escarificadas sembradas en ambos sustratos no mostraron diferencias significativas respecto al control en papel. Sin embargo, Sobrevilla-Solís et al (2013) propusieron la escarificación mecánica como un método adecuado para estimular la germinación en Prosopis, extremando cuidados para no afectar la calidad fisiológica de las semillas (Dutra et al 2007) Además, Rodríguez Araujo et al (2017 indicaron que la técnica de escarificación puede variar según la persona que la realiza, obteniendo con estos métodos elevados porcentajes de germinación en distintas especies de Prosopis. Por lo tanto, esto podría explicar los altos porcentajes de semillas duras obtenidas en la presente investigación.…”
Section: Discussionunclassified
“…Entre los tratamientos pregerminativos más utilizados para superar la dormición física, se encuentran la escarificación mecánica, térmica y la química (Sanabria et al 2004, Dutra et al 2007, Muñoz et al 2009, Pereira et al 2016, Trombin Souza et al 2018. Algunos autores describen los requerimientos germinativos de diferentes especies de Prosopis (Bravo et al 2011, Sobrevilla Solís et al 2013, Rodríguez Araujo et al 2017) y sugieren la importancia del estudio particular para cada especie y ambiente.…”
Section: Introductionunclassified